Effects of Multilevel Pulse Width Modulation on Iron Losses in Stator Cores - Stahre,Peter (CODEN:LUTEDX/TEIE, 2025)
The global energy transition and the growing adoption of electric vehicles drives an ever-increasing demand for more efficient electrical machines. A key improvement area is understanding and reducing iron losses in machine magnetic materials, such as those caused by Pulse Width Modulation (PWM). This thesis investigates the effects of PWM on magnetic hysteresis and the resulting iron losses in FeSi laminated stator core materials, with emphasis on the effects of switching frequency, modulation index and modulation levels. An experimental setup allowing for magnetic excitation of toroidal and stator cores was used. Measurements were conducted with sinusoidal waveforms and emulated cascaded H-bridge PWM with frequencies up to 600 Hz and switching frequencies between 4 kHz and 16 kHz. The results show that the increased iron losses from the harmonic content present in the PWM signal can be mitigated with an increased modulation index or switching frequency, where an increased modulation has a larger impact. Furthermore, increasing the number of cascaded H-bridges drastically reduced iron losses as well as the impact of increasing the switching frequency or modulation index. The study contributes to a deeper understanding of how different PWM parameters affect magnetic induction and power losses, providing material and insight that can assist in improving the efficiency of future EV applications.
Keywords: Pulse Width Modulation; Hysteresis; Core losses; Iron losses; PWM; Multi-level PWM; Laminated steel; Stator cores; Cascaded H-bridge